Examining employer experiences in the polytechnic sector's industrial training program - Katahama, Zhow; Bozorgzadeh, Tahora (Annals of Management and Organization Research, 2023)
Purpose: Industrial training, a structured educational program, provides supervised hands-on training within specified time frames and is available in both the private sector and government settings. Its primary aim was to bridge the gap between theoretical knowledge and practical skills, enabling participants to apply classroom learning in real-world scenarios. This experiential approach fosters competency development and a deeper understanding of industrial practices, teamwork, and professional ethics, ultimately preparing individuals for successful careers in various sectors. Research Methodology: Data analysis was conducted using a statistical software tool tailored for predictive modeling and analysis. This dedicated software package was employed to scrutinize and interpret the dataset, allowing for the extraction of meaningful insights and predictions. This analytical approach involves a series of statistical techniques, algorithms, and models to uncover patterns, correlations, and trends within the data. Results: From the perspective of instructors, industrial training has been noted as a catalyst for enhancing students' proficiency in both formal and informal communication, aiding them in identifying suitable research areas for their projects and honing their abilities in socialization and relationship-building. Limitations: The applicable and functional setting for the findings of this study lies within the realm of educational settings. Contribution: Our conclusions highlight the pivotal role of industrial training in enhancing students' abilities and knowledge following their training programs. We advocate recognizing industrial training as a valuable instrument for augmenting employees' skills and capabilities.